2001
DOI: 10.1002/hbm.1020
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear temporal dynamics of the cerebral blood flow response

Abstract: Abstract:The linearity of the cerebral perfusion response relative to stimulus duration is an important consideration in the characterization of the relationship between regional cerebral blood flow (CBF), cerebral metabolism, and the blood oxygenation level dependent (BOLD) signal. It is also a critical component in the design and analysis of functional neuroimaging studies. To study the linearity of the CBF response to different duration stimuli, the perfusion response in primary motor and visual cortices wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
108
1
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(129 citation statements)
references
References 33 publications
(48 reference statements)
17
108
1
2
Order By: Relevance
“…5. The BOLD response typically exhibits a temporal nonlinearity such that an appropriately shifted and added response to a brief stimulus over-predicts the true response to an extended stimulus (Birn et al, 2001;Boynton et al, 1996;Friston et al, 1998;Glover, 1999;Miller et al, 2001;Robson et al, 1998;Vasquez and Noll, 1998). This temporal nonlinearity is most pronounced when the brief stimulus is less than about 4 s and the extended stimulus is longer than 6 s. Comparing short and long duration stimuli that are both longer than about 4 s, the temporal nonlinearity is reduced.…”
Section: Experimental Characterization Of the Hemodynamic Responsementioning
confidence: 99%
See 2 more Smart Citations
“…5. The BOLD response typically exhibits a temporal nonlinearity such that an appropriately shifted and added response to a brief stimulus over-predicts the true response to an extended stimulus (Birn et al, 2001;Boynton et al, 1996;Friston et al, 1998;Glover, 1999;Miller et al, 2001;Robson et al, 1998;Vasquez and Noll, 1998). This temporal nonlinearity is most pronounced when the brief stimulus is less than about 4 s and the extended stimulus is longer than 6 s. Comparing short and long duration stimuli that are both longer than about 4 s, the temporal nonlinearity is reduced.…”
Section: Experimental Characterization Of the Hemodynamic Responsementioning
confidence: 99%
“…The two sources of nonlinearity can be distinguished experimentally by whether the nonlinearity is present in just the BOLD response or in both the BOLD and CBF responses. For example, Miller et al (2001) found that both visual and motor cortices exhibited a nonlinear BOLD response, but only the visual cortex showed a nonlinear CBF response.…”
Section: Transients Of the Bold Responsementioning
confidence: 99%
See 1 more Smart Citation
“…A large increase in CBF is not accompanied by a proportionally large increase in BOLD signal change due to the washing out of all the deoxyhemoglobin in the venous vasculature. 13,14 This mismatch is a matter of concern, as motor execution is a fundamental paradigm for many BOLD fMRI studies and is of clinical relevance in the prognosis of neurologic disorders such as Parkinson's disease. 15,16 To date, the matter remains open to debate.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are many reports of nonlinearity in haemodynamic responses in the literature (e.g. Ances et al, 2000;Huettel and McCarthy, 2000;Miller et al, 2001;Pfeuffer et al, 2003;Vazquez and Noll, 1998), and so it is unlikely that a simple linear convolution model (LCM) is general.…”
Section: Introductionmentioning
confidence: 99%